Sleep it off: Bullying and sleep disturbances in adolescents. (29th July 2018) - Donoghue, Christopher; Meltzer, Lisa J.
ABSTRACT: Introduction: Involvement in bullying is associated with negative health outcomes for adolescents. Recent studies suggest that bullying is related to sleep disturbances. The purpose of this study was to examine differences in sleep disturbances (bedtime fears, insomnia, parasomnias) between victims, bullies, and youth not involved in bullying, as well as to explore differences across various types of bullying behavior (verbal, physical, social, cyber). Methods: High school students ages 14–17 years (mean = 16.0) in the United States (n = 885; 57.3% female; 87.5% White) completed The Children's Report of Sleep Patterns and questions about involvement in verbal, physical, social and cyberbullying. Results: Differences in all three sleep disturbances were found across groups, with victims and bully‐victims reporting more sleep disturbances than bullies and youth not involved. A similar pattern was found across all bullying types, with more sleep disturbances for victims and bullyvictims. Conclusions: The results of this cross‐sectional study highlight the importance of screening youth for sleep disturbances that may indicate daytime issues with bullying or victimization, as well as the need for longitudinal studies to elucidate potential pathways between sleep and bullying/victimization.